Medium Affect Desire: Hybridising Real Virtual and the Actualised through Affective Medium Ecology - Marc Boumeester (Footprint)
Underneath the turbulent surface of the ubiquitous media-scape lies an even more agile and aggressive set of relations. A central figure in this turmoil of desires seems to be the asignifying sign, which has a hybridising liaison with both the realm of the real virtual and the realm of the actualised. The main question is what does it want? This new materialistic, non-anthropocentric liberty of affect is creating an arena of strange attractors and other topological vector fields in which our own unconscious drive is as effective as that of the steel ball in a pinball machine. Could we isolate the intrinsic drive of the medium from its subservient position in the aesthetic, freeing its desire from the anthropocentric dominion? What does it Yen for? Perhaps this gap is not meant to be filled, as it is this yearning what it yearns for. The asignifying sign cannot be isolated, it is neither here nor there, yet it is conditionally omnipresent, it inhibits the gap, its desire is to affect.